IMPLEMENTASI MODEL OUTDOOR LEARNING PADA PEMBELAJARAN GEOGRAFI BERBASIS LINGKUNGAN SEKOLAH UNTUK MENINGKATKAN SIKAP PEDULI PESERTA DIDIK SMAN 14 BULUKUMBA - A Nurul Iftitah Syam; Muhammad Yusuf; Rosmini Maru; Hasriyanti Hasriyanti; Sukri Nyompa (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The low level of students' concern for school environmental sanitation and the lack of visualization of real geosphere phenomena in conventional teaching are the background of this research. These operational problems trigger students' indifference in maintaining ecosystem sustainability and reduce the effectiveness of material absorption. The main focus of this scientific study is to analyze the implementation of the outdoor learning model in school-based Geography learning and to test the disparity in environmental care attitudes between the experimental and control classes at SMAN 14 Bulukumba. The steps of the quasi-experimental quantitative approach with a pretest-posttest control group design are operated through purposive sampling. Primary field data collection is collected through a four-level Likert scale questionnaire, which is then analyzed using parametric requirements tests, Independent Sample t-tests, and N-Gain values. Quantitative data empirically reveals an increase in the average of the experimental class which shot up from 73.90 to 86.47 with an N-Gain score of 0.48 (medium category), far exceeding the control class which only increased from 72.77 to 77.47 with an N-Gain of 0.17 (low category). A t-test demonstrated a significant difference in performance between the two groups at 0.000. The main conclusion confirms that experiential learning, an out-of-class learning method, has proven highly effective in fostering ecological awareness. Secondary education practitioners are recommended to consistently draft implementation plans for learning activities based on living laboratories. ABSTRAK Rendahnya kepedulian peserta didik terhadap sanitasi lingkungan sekolah serta minimnya visualisasi fenomena geosfer nyata pada pengajaran konvensional melatarbelakangi penelitian ini. Masalah operasional tersebut memicu ketidakpedulian siswa dalam menjaga kelestarian ekosistem dan menurunkan efektivitas penyerapan materi. Fokus utama kajian ilmiah ini adalah menganalisis implementasi model outdoor learning pada pembelajaran Geografi berbasis lingkungan sekolah serta menguji disparitas sikap peduli lingkungan antara kelas eksperimen dan kontrol di SMAN 14 Bulukumba. Langkah-langkah pendekatan kuantitatif kuasi eksperimen dengan desain pretest-posttest control group design ini dioperasikan melalui penarikan sampel secara purposive sampling. Pengumpulan data primer lapangan dihimpun lewat angket kuesioner skala Likert empat tingkat, yang selanjutnya dianalisis menggunakan uji persyaratan parametrik, Independent Sample t-test, dan nilai N-Gain. Data kuantitatif secara empiris menyingkap peningkatan rata-rata kelas eksperimen yang melesat dari 73,90 menjadi 86,47 dengan skor N-Gain 0,48 (kategori sedang), jauh melampaui kelas kontrol yang hanya naik dari 72,77 ke 77,47 dengan N-Gain 0,17 (kategori rendah). Uji-t membuktikan signifikansi perbedaan performa kedua kelompok pada angka 0,000. Simpulan utama menegaskan bahwa metode belajar luar kelas melalui pengalaman langsung (experiential learning) terbukti sangat andal menumbuhkan kesadaran ekologis. Praktisi pendidikan menengah direkomendasikan merancang draf rencana pelaksanaan pembelajaran berbasis aktivitas laboratorium hidup secara konsisten.